Playing the game? A criminological account of the making and sharing of Probationary: The Game of Life on Licence. (December 2020) - Jackson, Will; Murray, Emma; Hayes, Anne
This article reflects on the production and dissemination of Probationary: The Game of Life on Licence . Probationary is an artwork in the form of a board game that takes its players on a journey as they navigate the complexities of the probation process. This article explores the interdisciplinary collaborations that underpinned both the making and the sharing of the game and examines the benefits and challenges of working with stakeholders in this way. We suggest that creative methodologies can provide new ways of engaging with research subjects and new means of disseminating academic research with a view to informing change.